Living older in the family context: dependency in self-care - Araújo, Isabel; Paúl, Constança; Martins, Manuela (Revista da Escola de Enfermagem da USP, 2011)
The purpose of this study is to help improve nursing care to dependent people and their families. The study objectives were: to describe the degree of dependency of the elderly in the family context; to identify the sociodemographic characteristics of the dependent elderly in the family context; to describe the main cause of dependency in the aged at home. This is a exploratory, descriptive study with a quantitative approach. In the period comprised between October 2007 and June 2008, 108 families from a northern region of Portugal were selected, with an elderly dependent. It was a convenience sample. For the collection of information, we used a questionnaire with the Barthel Index. Results showed that older people are predominantly women, widows, in average 81 years old, with severe level of dependence, and the leading cause of dependence was circulatory system diseases.